Risk factors for in-season injury in varsity collegiate cross-country athletes: an analysis of one season in 97 athletes - Hayes, L. E.; Boulos, A.; Cruz, J. A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Cross-country runners experience high rates of injury. This prospective cohort study aimed to identify pre-season risk factors for in-season injury in a cohort of collegiate cross-country athletes. METHODS: Pre-season and post-season electronic surveys were designed and administered to 297 NCAA Division I and III runners in August and November 2016, respectively. Pre-season surveys queried athletes` training methods, lifestyle habits, and history of previous injuries. Post-season surveys queried occurrence of new injuries sustained during the season. The risk of new injury was examined based on weekly mileage, sleep, diet, training routines, BMI, and history of previous injuries. RESULTS: Fifty-three percent of athletes sustained a new injury (acute injury or exacerbation of a chronic injury) during the season. In univariate analysis, the existence of a pre-season injury (RR 1.57, 95% CI 1.11-2.23, P=0.01), large mileage increases (RR 1.55, 95% CI 1.09-2.22, P=0.02), and poor sleep quality (P=0.04) were significantly associated with higher risk for injury among collegiate cross-country athletes. CONCLUSIONS: Cross-country athletes with an existing injury during the pre-season, large mileage increases during the season, and poor sleep quality may be at increased risk of sustaining a new acute injury or exacerbate an existing injury during the cross-country season. Coaches, athletic trainers, and athletes can use these results to modify training regimens and lifestyle factors to decrease the risk of injury.